INOVASI APLIKASI PROGRAM SIBALONG PADA POLRES TABALONG - Nurhalifah (stiatabalong.ac.id, 2025)
To address the issue of lengthy service queues at the Tabalong Police Station, the SIBALONG application was introduced. This application, developed by the Tabalong Police, serves as a service innovation aimed at enhancing public service delivery within Tabalong Regency. This study investigates the impact of the SIBALONG application in streamlining various services, including SIM (Driving License) registration, SKCK (Police Clearance Certificate) processing, and permit applications for public events. Furthermore, the latest version of the application features a panic button, enabling rapid response to public complaints. Continuous promotion of the SIBALONG application is carried out through social media and by community police officers (Bhabinkamtibmas) at the village and sub-district levels to ensure public understanding of its usage. This research employs a descriptive qualitative method with data collection techniques encompassing field observations, interviews, and document analysis. Data were gathered from five police personnel and five members of the public who utilized the services, focusing on a comprehensive understanding of the phenomenon. Data analysis involved descriptive methods, addressing issues related to social phenomena, human behavior, and aspects not quantifiable through numerical data. The findings indicate that the SIBALONG application has been well-received by service users, particularly those residing far from service locations, who reported significantly improved access to services. Although this service innovation has limitations related to internet connectivity, these issues are primarily observed in areas with limited internet access. Keywords: Innovation, Program, Service